Health, shocks, and poverty persistence - Dercon, Stefan; Hoddinott, John F. (Oxford University Press, 2005)
This book evaluates alternatives in widening insurance and social protection provision - including sustainability and poverty effects, in thematic papers and case studies, development assessments, and policy analyses